143k views
3 votes
How to factorise 9x^3-x

User Phamductri
by
5.2k points

1 Answer

3 votes

Answer:

x(3x+1)(3x-1)

Explanation:

factor x out = 9x^2 -1. notice that 1 * x = 1, thats why theres a 1 now.

(This is called the difference of two squares. Since 1 is a square(1^2 = 1).)

Next factor the first part = 3 * 3 = 9 x * x = x^2.

So far we have x(3x - )(3x + ). The blank spaces show what we don't know.

The second part is easy. 1 * 1 = 1, so we fill in the spaces to get x(3x+1)(3x-1)

happy new years eve!

User Ajmal Noushad
by
6.5k points